Anteseden Kepuasan Pengguna Aplikasi E-Wallet - Cahya Putra, Dewa Kadek Aditya; Suputra, Gusti Alit; Benni Kusyana, Dewa Nyoman (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
User satisfaction is influenced by many factors, including system quality, information quality, and perceived usefulness. The purpose of this study was to determine the effect of system quality, information quality, and perceived usefullness on user satisfaction of LinkAja!. This research was conducted in Denpasar City on users of the LinkAja! e-wallet application! with a population that is not known with certainty and by using a sample determination based on the number of parameters, a sample of 134 LinkAja users is obtained! and sampling was done by purposive sampling and convenience sampling. Primary data collection was carried out by conducting interviews at the pre-survey stage and using questionnaires where the results of respondents' answers were then used to carry out validity and reliability tests, followed by classical assumption tests and hypothesis testing using multiple linear regression analysis. The results of the analysis prove that partially and simultaneously system quality, information quality, and perceived usefullness have a positive and significant effect on LinkAja user satisfaction!